1989
DOI: 10.1007/bf00442815
|View full text |Cite
|
Sign up to set email alerts
|

Diazepam induces a dissociation between explicit and implicit memory

Abstract: The effects of 0.2 mg/kg orally administered diazepam and of a placebo on explicit memory, implicit and knowledge memory were assessed using a free recall task, a word-stem completion task and two category-generation tasks. Twenty four healthy volunteers took part in this double-blind study. Diazepam impaired explicit but not implicit memory. The drug also spared knowledge memory. Explicit memory was linked with the diazepam-induced sedation and with the self-rated affective load of to-be remembered words, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…As expected, the difference in delayed recall between the groups was larger in the post-drug condition than in the pre-drug condition (see Fig. 1 In other studies (Fang, Hinrichs and Ghoneim, 1987;Danion et al, 1989Danion et al, , 1990Sellal et al, 1992), it was found that diazepam did not affect repetition priming. However, in all these studies, repetition priming was assessed using a word or stem completion task, while in the present study a lexical decision task was used.…”
Section: Discussionsupporting
confidence: 68%
“…As expected, the difference in delayed recall between the groups was larger in the post-drug condition than in the pre-drug condition (see Fig. 1 In other studies (Fang, Hinrichs and Ghoneim, 1987;Danion et al, 1989Danion et al, , 1990Sellal et al, 1992), it was found that diazepam did not affect repetition priming. However, in all these studies, repetition priming was assessed using a word or stem completion task, while in the present study a lexical decision task was used.…”
Section: Discussionsupporting
confidence: 68%
“…The dose of diazepam used clinically in humans to relieve anxiety is about one tenth that used here, and diazepam in this dose range has been found to be mildly sedating (Danion et al 1989) in humans. Non-human primates show significant deficits in response time during various tasks in the 1.0 to 2.0 mg/ kg dose range (Wayner et al 1989;Hudzik and Wenger 1993), and these longer response times have been considered an indication of diazepam's sedating effects.…”
Section: Diazepammentioning
confidence: 68%
“…Diazepam has been found to impair performance on various tests of attention, vigilance, learning and working memory (Coull et al 1995a, b;Danion et al 1989;Roy-Byrne et al 1987;Kozena et al 1995). Diazepam (1.0 mg/kg) impaired performance and responding on a delayedmatch-to-sample task in rhesus monkeys (Hudzik and Wenger 1993).…”
Section: Diazepammentioning
confidence: 99%
“…However, much basic research attests to the fact that acute doses of alcohol and the structurally and functionally similar benzodiazepines have significant effects on human memory abilities. Initial research suggested that alcohol (Hastroudi, Parker, DeLisi, Wyatt, & Mutter, 1984) and the benzodiazepines (Danion, Zimmerman, Willard-Schroeder, Grange, & Singer, 1989;Fang, Hinrichs, & Ghoneim, 1987; also see a review by Curran, 1991) significantly impaired performance on traditional tests of explicit memory, while leaving performance on implicit memory tasks intact. However, recent evidence suggests that certain benzodiazepines may not only reduce explicit memory performance but also impair implicit memory processes when memory is tested at peak drug concentrations (e.g., Legrand et al, 1995;Stewart, Rioux, Connolly, Dunphy, & Teehan, 1996).…”
Section: Cognitive Effects Of Alcohol In Ptsdmentioning
confidence: 99%